Integrating global perspectives in biomedical science education: the role of project-based learning in addressing Western-centric paradigms and enhancing student preparedness for global health challenges - Lalujan, Joanne Daniella; Pranjol, Md Zahidul I. (Frontiers in Education, 2025)
Biomedical Sciences education has traditionally focused on Western paradigms, often overlooking the health challenges faced in less economically developed countries. Integrating global perspectives is essential, yet institutional guidelines lack clear directives for doing so. This perspective paper proposes a project-based learning (PBL) approach within undergraduate biomedical sciences modules, which focuses on tropical infectious diseases to promote decolonized learning by contrasting the Global North and South. In this model, students will work collaboratively to learn problem-solving techniques relevant to real-world issues like tropical diseases. Although in theory PBL is a useful way of learning, there are potential challenges with group dynamics and engagement. This paper discusses the various benefits and limitations of implementing this approach.